Condições clínicas orais de pacientes com histoplasmose disseminada e AIDS em hospital de referência de Fortaleza - Freitas, Aglaê Francelino (2010)
The disseminated histoplasmosis (DH) is a serious opportunistic infection caused by Histoplasma capsulatum, often seen in aids patients in advanced immunosuppression treated in health care service for people living with HIV/aids in Fortaleza, Ceará. Like other opportunistic infections, histoplasmosis can be identified early by the presence of specific manifestations in the oral cavity. To know the frequency and characteristics of oral manifestations of DH aids-associated it was carried out a cross-sectional study in adult patients who were suspected or confirmed to have DH, from August 2009 to March 2010. The data were collected through questionnaire, oral clinical examination, histocyto-pathological examinations, photographs and observation of medical records. Twenty-two cases of DH were diagnosed in the total of fifty-six patients. Five out of the twenty-two patients (5/22, 22.7%) had oral lesions with clinical features of histoplasmosis and in four out of the twenty-two (4/22, 18.9%) the fungus was detected through biopsy and exfoliative cytology, in fragments and smears examined by staining with Grocott, PAS (Periodic Acid-Schiff) and Giemsa. Nine patients were defined as possible cases of DH (based on pathological background and clinical manifestations) and two of those presented, in the same way, oral lesions with clinical features of histoplasmosis, however, these were not biopsied. Ulcer with hemorrhagic crust on the lip mucosa was the most frequent (60%), followed by granulomatous form with multiple lesions on the palate and gums (20%) and ulcerated lesion on the tongue (20%). DH patients had a median of 36.5 cells / mm³ of lymphocyte T CD4 and significantly higher levels of lactate dehydrogenase (LDH; p= 0.0001) and aspartate aminotransferase (AST/TGO; p= 0.0002), as well as significantly lower levels of hemoglobin (p= 00.2), leukocytes (p= 0.04) and platelets (p= 0.001). Odynophagia was reported by all patients with DH(p = 0.000), and dysphagia was present in ten (45.4%, p = 0.011). Dysphonia was observed in a patient who presented histoplasmosis of the larynx. Pseudomembranous candidiasis, followed by the erythematous form was associated with DH in 45.5% and 4.5% of the patients, respectively. The prevalence of gingivitis was 38.3% and in 57.4% of the patients was identified calculus dental which indicates poor oral health and significant need for dental services.